The effect of neuromuscular blocking reversal agents on perioperative neurocognitive function after general anaesthesia: a systematic review and meta-analysis - Hao Wang; Xinghua Lv; Lin Wu; Fangli Ma; Ling Wang; Yongqi Wang; Xiaoxia Wang; Yulan Li (BMC Anesthesiology)
Abstract Background Perioperative neurocognitive dysfunction (PND) is influenced by various perioperative factors. Recent studies suggest that neuromuscular blocking reversal agents (NMBRs) may impact on PND. However, the results have been inconsistent. Therefore, we aimed to compare the effects of perioperative NMBRs on PND through this systematic review and meta-analysis. Methods We searched PubMed, CENTRAL, Embase, Web of Science, Scopus, and China Biology Medicine from their inception until May 2024. Two reviewers independently identified randomized controlled trials (RCTs) that compared the perioperative use of NMBRs with either a placebo or other NMBRs in patients undergoing general anaesthesia. We assessed the certainty of the evidence using the Grading of Recommendations Assessment, Development and Evaluation (GRADE) methodology. The primary outcome was the incidence of PND within 7 days following surgery, while the secondary outcomes included the time required to achieve a Train-of-Four ratio (TOF) ≥ 0.9 after administration of NMBRs, length of stay (LOS) in both the post-anaesthesia care unit (PACU) and the hospital, as well as the risk of adverse events (i.e. postoperative nausea and vomiting (PONV) and mortality). Results A total of 10 randomized controlled trials involving 1705 patients compared the effects of NMBRs on PND. Neostigmine and sugammadex are the most commonly used NMBRs in clinical anaesthesia practice. In the primary analyses of all regimens, sugammadex significantly reduced the incidence of PND compared to neostigmine (risk ratio [RR] 0.67; 95% confidence interval [CI]:0.48–0.94; I 2 = 0%; P = 0.02; moderate quality). However, the results indicated that there is no significant association between neostigmine and PND when compared to placebo (RR 0.76; 95% CI: 0.55–1.05; I 2 = 35%; P = 0.09; moderate quality). The secondary outcomes revealed that sugammadex could significantly shorten the time of TOF ≥ 0.9 compared to neostigmine (mean difference [MD] -4.52; 95%CI: -5.04 to -3.99; I 2 = 80%; P < 0.01; Moderate quality). Furthermore, no significant differences were observed in the incidence of adverse events or hospital LOS. Conclusions This meta-analysis demonstrated that the use of sugammadex was associated with improved early perioperative neurocognitive function compared to neostigmine when used to reverse neuromuscular blockade, without an increase in the incidence of adverse events. Systematic review protocol PROSPERO CRD42024520287.